2007
DOI: 10.1016/j.cardiores.2007.02.015
|View full text |Cite
|
Sign up to set email alerts
|

NADPH oxidase mediates angiotensin II-induced endothelin-1 expression in vascular adventitial fibroblasts

Abstract: Ang II-evoked expression of ET-1 in adventitial fibroblasts appears to be mediated, at least in part, by NADPH oxidase. Functionally, this mechanism stimulates collagen expression thereby implicating the adventitia as a potential contributor to the vascular pathophysiology associated with oxidative stress and vascular remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 51 publications
3
40
0
2
Order By: Relevance
“…Recently, it has been reported that Ang II stimulation evokes expression of ET-1 in adventitial fibroblasts contributes to type I procollagen expression through activation of ET A receptors, suggesting a functional role for adventitial ET-1 release in the regulation of the extracellular matrix [15] . Expression of ET-1 in adventitial fibroblasts is mediated by ·O 2 - [16] , consistent with the findings in many different cell types [17] , including VSM [18,19] . However, the mechanisms of oxidative stress regulating ET-1 production are still unclear.…”
Section: Perivascular Fibroblasts: Source Of Ros and Regulation Of Vasupporting
confidence: 89%
“…Recently, it has been reported that Ang II stimulation evokes expression of ET-1 in adventitial fibroblasts contributes to type I procollagen expression through activation of ET A receptors, suggesting a functional role for adventitial ET-1 release in the regulation of the extracellular matrix [15] . Expression of ET-1 in adventitial fibroblasts is mediated by ·O 2 - [16] , consistent with the findings in many different cell types [17] , including VSM [18,19] . However, the mechanisms of oxidative stress regulating ET-1 production are still unclear.…”
Section: Perivascular Fibroblasts: Source Of Ros and Regulation Of Vasupporting
confidence: 89%
“…Indeed, over-expression of SOD in mouse aortic adventitial fibroblasts inhibits the ANG IIinduced type I procollagen α-I protein expression and . O 2 -generation [188].…”
Section: Ang Ii-induced Collagen Production and Degradation During Inmentioning
confidence: 99%
“…10 -12 Apart from inducing vasoconstriction, ET-1 activates vascular NADPH oxidase, leading to an increase in oxidative stress through enhanced reactive oxygen species (ROS) production. 13,14 Because oxidative stress is generally increased in hypertension and plays a pathogenic role in the development and progression of cardiovascular disease, we hypothesized that enhanced formation of ROS contributes to the sunitinib-induced cardiovascular adverse effects. 15 To further explore the cardiovascular adverse effects of sunitinib, we performed detailed studies in chronically instrumented awake swine.…”
mentioning
confidence: 99%